D6.10 Mass media material - Tzouvaras, Marios; Nisantzi, Argyro; Christofe, Andreas; Evagorou, Evagoras G.; Mettas, Christodoulos; Themistocleous, Kyriacos; Papoutsa, Christiana; Lysandrou, Vasiliki; Agapiou, Athos; Lasaponara, Rosa; Masini, Nicola; Krauss, Thomas; et al. (My University, 2018)
The specific deliverable summarizes the material related to the form of interviews and articles in newspapers and magazines of the project. Radio, journals and newspapers are also used as means to promote and advertise some of the dissemination events of the project. Mass media promotions at a national level as well in the European Research Media Centre are organized to promote and raise awareness. Guest appearances on TV and radio shows and national newspapers are used to ensure the access to the widest community.
Keywords: ATHENA project; Mass media